Unusual giant multilocular thymic cyst with mature teratoma including a carcinoid component in the mediastinum - Takehiko Manabe; Kenta Kajiyama; Takashi Iwanami; Takeshi Hanagiri; Tatsuhiko Sako (Surgical Case Reports)
Abstract Background Teratoma is the second most common mediastinal neoplasm, but malignant transformation in mature teratomas is uncommon, and cases of carcinoid tumor with teratoma are described in only a few studies. In addition, multilocular thymic cyst associated with mature mediastinal teratoma is also a rare entity. There have been no reports of case with the coexistence of these three pathological lesions. Case presentation The patient was a 24-year-old man who was referred to our hospital due to a 2-day history of left shoulder pain, a feeling of severe chest tightness and high fever. Pre-operative computed tomography (CT) showed a large, fluid-filled and well-demarcated multilocular cyst in the anterior to superior mediastinum measuring up to 12 cm in size. Contrast-enhanced CT also revealed that the tumor contained a solid component with slight contrast enhancement and spotty wall-thickening septation. Therefore, cystic thymoma, thymic cyst, cystic teratoma, or germ cell tumor with an inflammatory reaction were considered as differential diagnoses. The patient underwent tumor extirpation under median sternotomy. The pathological diagnosis was multilocular thymic cyst with mature teratoma including carcinoid tumor (Grade 2) in the mediastinum. Conclusions The relationship between thymic cyst, teratoma and carcinoid tumor is unclear at present; therefore, further research is needed to clarify the relationship between these entities. In this report, we present a case of multilocular thymic cyst with mature teratoma including a carcinoid component in the mediastinum that was detected by complete surgical resection.